ANALISIS PENGARUH PUBLIC RELATION PERCEPTION DAN BRAND IMAGE TERHADAP CUSTOMER LOYALTY (STUDI PADA KONSUMEN INDOSAT DI KOTA SEMARANG) - Dwi Prawani Sri Redjeki; Jefri Heridiansyah (STIE Pelita Nusantara Semarang, 2017)
This research examines the influence of consumer perception about public relation activity of a company to customer loyalty and test effect brand image to customer loyalty. This study uses questionnaires as a medium to collect data from consumers. Questionnaires were distributed to 40 Indosat customers in Semarang City who have used or used Indosat for at least 1 (one) year.The results of this study show that consumer perceptions of public relations activities of a company have a positive effect on customer loyalty. The influence of public relation perception (PRP) on customer loyalty will be more powerful and significant if the brand image is high. If the image brand is low, the influence of PRP on customer loyalty is meaningless. Public relations perception positively affects customer loyalty, meaning that the lower the perception of consumers about public relations activities of a company will be lower the level of customer loyalty. Conversely, the higher the public relation perception of a company in the eyes of its customers, the higher the level of customer loyalty.Brand image has a positive effect on customer loyalty. That is, when consumers have a high brand image of a product, will increase customer loyalty. Conversely, when consumers have a low brand image in mind, it will have a small effect on customer loyalty